2021
DOI: 10.1088/1475-7516/2021/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Proper time reparametrization in cosmology: Möbius symmetry and Kodama charges

Abstract: It has been noticed that for a large class of cosmological models, the gauge fixing of the time-reparametrization invariance does not completely fix the clock. Instead, the system enjoys a surprising residual Noether symmetry under a Möbius reparametrization of the proper time, which maps gauge-inequivalent solutions to the Friedmann equations onto each other. In this work, we provide a unified treatment of this hidden conformal symmetry and its realization in the homogeneous and isotropic sector of the Einste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In the case of FLRW cosmology with curvature k, we only have a single scale factor a, so the field space is one-dimensional and (3.33) easily applies. This also extends to the case of a non-vanishing cosmological constant, where it reproduces the results of [49]. On the other hand, without any matter content the dynamics itself is trivial.…”
Section: Flrw Cosmology With Scalar Fieldsupporting
confidence: 82%
See 1 more Smart Citation
“…In the case of FLRW cosmology with curvature k, we only have a single scale factor a, so the field space is one-dimensional and (3.33) easily applies. This also extends to the case of a non-vanishing cosmological constant, where it reproduces the results of [49]. On the other hand, without any matter content the dynamics itself is trivial.…”
Section: Flrw Cosmology With Scalar Fieldsupporting
confidence: 82%
“…This latter is spanned by the Hamiltonian H together with the volume V and the generator C of isotropic dilations on phase space. This was extended in [49] to include spatial curvature and a cosmological constant. In [50], the present authors have studied the Kantowski-Sachs model describing the black hole interior, and found that there the CVH algebra gets extended to an iso(2, 1) algebra of conserved charges encoding the dynamics of the system in an algebraic manner.…”
Section: Introductionmentioning
confidence: 99%
“…However, should the action (4.7) exhibit a hidden conformal symmetry, it could very well be that the connection to FLRW cosmology could already be established at this point. This would follow along the lines of recent results on mapping of FLRW cosmology onto conformal mechanics, see [111][112][113]. 19 Given the similarities of the equation of motion of the condensate field (4.12) to the non-linear Schrödinger or Klein-Gordon equations [114], it might likewise admit solitary wave solutions.…”
Section: Effective Cosmological Equations and Volume Dynamicsmentioning
confidence: 74%
“…In a recent work [46] it has been unraveled that the black hole interior homogeneous model actually posses a non-trivial and finite dimensional symmetry algebra, isomorphic to the iso(2, 1) Poincaré algebra, that fully encodes the dynamics on the phase space. This is a generalization of what happens in flat FLRW cosmology coupled with a scalar field, in the isotropic case and for Bianchi I model [47][48][49][50][51][52][53][54], and it has very recently extended to (A)dS Schwarzschild solutions [55].…”
Section: Introductionmentioning
confidence: 92%